PENGGUNAAN MEDIA GAMBAR OBJEK WISATA PANTAI LASIANA DALAM KEMAMPUAN MENULIS PUISI SISWA KELAS VIII SMP NEGERI 20 KUPANG - Nirmala Maria Abong Duan Duan; Labu Djuli; Dian Sari Pekuwali (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2026)
The focus of this study is “How is the Use of Media Image of Lasiana Beach Tourist Attractions in the Poerty Writing skills of Class VIII SMP Negeri 20 Kupang.” The purpose of this study is to describe students’ ability in writing poetry through the use of image media. The theory applied in this research is writing theory, as it is beneficial for developing thinking skills, managing emotions, increasing creativity, supporting problem-solving abilities, and providing personal satisfaction. Writing activities aim to encourage students to express their feelings and convey information. The research method used in this study is descriptive qualitative. In this research, the researcher selected poetry writing material by developing the Merdeka Curriculum applied in Grade VIII during the odd semester, Phase D 4.2. Students were able to write poetry using appropriate aspects. Poetry is a form of literary art used to express feelings and imagination through written language. Based on the analysis conducted on 22 eighth-grade students of SMP Negeri 20 Kupang, the students were considered capable of writing poetry by paying attention to writing rules and aspects. These results can be seen from the percentage of achievement, which shows a success rate of 7.918%. Students were able to write poetry with scores ranging from 70 to 100. A total of 16 students achieved mastery in poetry writing with a percentage of 72%, while 6 students did not achieve mastery with a percentage of 27%.